Bail: law and procedures with tips to avoid police harassment - Jai, Janak Raj (New Delhi, 2013)
The chapters including Bail, Parole and Furlough, Bail for Non-bailable Offences, Anticipatory Bail, Cancellation of Bail, Bail Bond, Role of Police and its Power and Duties, Police Interrogation.
Keywords: Bail